Ecological impacts of invading seaweeds: a meta‐analysis of their effects at different trophic levels. Issue 1 (10th October 2014) - Maggi, E.; Benedetti‐Cecchi, L.; Castelli, A.; Chatzinikolaou, E.; Crowe, T. P.; Ghedini, G.; Kotta, J.; Lyons, D. A.; Ravaglioli, C.; Rilov, G.; Rindi, L.; Bulleri, F.
Abstract: Aim: Biological invasions are among the main threats to biodiversity. To promote a mechanistic understanding of the ecological impacts of non‐native seaweeds, we assessed how effects on resident organisms vary according to their trophic level. Location: Global. Methods: We performed meta‐analytical comparisons of the effects of non‐native seaweeds on both individual species and communities. We compared the results of analyses performed on the whole dataset with those obtained from experimental data only and, when possible, between rocky and soft bottoms. Results: Meta‐analyses of data from 100 papers revealed consistent negative effects of non‐native seaweeds across variables describing resident primary producer communities. In contrast, negative effects of seaweeds on consumers emerged only on their biomass and, limited to rocky bottoms, diversity. At the species level, negative effects were consistent across primary producers' response variables, while only the survival of consumers other than herbivores or predators (e.g. deposit/suspension feeders or detritivores) decreased due to invasion. Excluding mensurative data, negative effects of seaweeds persisted only on resident macroalgal communities and consumer species survival, while switched to positive on the diversity of rocky‐bottom consumers. However, negative effects emerged for biomass and, in rocky habitats, density of consumers other than herbivores or predators. Main conclusions: Our results support the hypothesis that seaweeds' effects on resident biodiversity are generally more negative within the same trophic level than on higher trophic guilds. Finer trophic grouping of resident organisms revealed more complex impacts than previously detected. High heterogeneity in the responses of some consumer guilds suggests that impacts of non‐native seaweeds at higher trophic levels may be more invader‐ and species‐specific than competitive effects at the same trophic level. Features of invaded habitats may further increase variability in seaweeds' impacts. More experimental data on consumers' response to invasion are needed to disentangle the effects of non‐native seaweeds from those of other environmental stressors.